Struktur Bangunan Ilmu Pengetahuan Manajemen Pendidikan Islam - Zaenal Arifin; Moh. Turmudi (Indonesian Journal of Humanities and Social Sciences, 2020)
This article discusses how the basic building structure of Islamic education management science. This is important considering that Islamic education management science is a very new science so it requires the involvement of all parties to build Islamic education management science with the aim of being able to be called a scientific discipline. To discuss it, the author contextualizes Archie J. Bahm's views on the basic building structure of science into the area of Islamic education management studies. Islamic education management science as a scientific discipline has a material object of all empirical facts regarding the management activities of Islamic educational institutions, while its material object is management science. Thus the building structure of Islamic education management science can follow the scientific building structure which is built on the basis of scientific principles and methods.